Efektivitas Penerapan Sistem Informasi Manajemen Daerah (SIMDA) untuk Pengelolaan Keuangan - Putu Ayu Puji Laksmi Dewi; Animah Animah; Yusli Mariadi (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
The effectiveness of SIMDA implementation is the result of the extent to which a public sector organization can produce financial reports in accordance with predetermined criteria and in order to assist information technology-based financial management. The purpose of this research to analyze the effectiveness of the implementation of SIMDA in the regional secretary of Mataram City, especially the general section. The research method used in this research is descriptive qualitative with a phenomenological approach. Data collection techniques are in the form of library research and observation consisting of indepth interviews and documentation. The result of this research indicate that the implementation of SIMDA at the City of Mataram, especially the general section has been running effectively. This can be seen from the employees who have understood the meaning of SIMDA, the success of the program, the success of the target, the satisfaction of using SIMDA, and the suitability of the results. Other factors owned by the regional secretary of Mataram City also support the effective implementation of SIMDA such as communication, resources, disposition, and bureaucratic structure.